The current status and further developments of geohazard monitoring and early warning program in China. Issue 4 (April 2020) - Bing, Han; Bin, Tong; Yanling, Zhang; Chunrong, Yin
Abstract: China is one of most severely threatened countries by geohazard in the world. To further improve the capacity of geohazard prevention and reduce potential damage, meteorological early warning on various scales, mass prediction and disaster prevention and professional monitoring have been implemented and achieved great progress, which lead to the great reduction in number of casualties. However, with the increase of engineering disturbance, tectonic activity and extreme climate events, the prevention and mitigation of geohazard should be further strengthened from different perspectives including the implementation of field investigation on geohazard triggering conditions, advancement and application of regional geohazard mapping, improvement of regional meteorological early warning, monitoring of geohazard development using integrated technologies involving remote sensing, LiDAR, InSAR, etc, and capacity of observation and monitoring by public.